2001
DOI: 10.1130/0091-7613(2001)029<0715:efmfot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiphase folding of the central Indian Ocean lithosphere

Abstract: Long-wavelength (100-300 km) folding in the central Indian Ocean associated with the diffuse plate boundary separating the Indian, Australian, and Capricorn plates is Earth's most convincing example of organized large-scale lithospheric deformation. To test the timing and mechanics of this deformation as implied by plate-kinematic and deformation models, we present a new analysis of the seismic stratigraphy of the Bengal Fan sediments. This shows that the folding of the oceanic lithosphere was multiphase, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 18 publications
1
69
0
Order By: Relevance
“…Cloetingh et al, 1999Cloetingh et al, , 2002Stephenson and Cloetingh, 1991;Lambeck, 1983;McAdoo and Sandwell, 1985;Ziegler et al, 1995;Bonnet et al, 2000;Gerbault, 2000;Krishna et al, 2001) to put forward a process of deformation through buckling of the entire lithosphere (known as lithospheric folding). These have been found within intraplate settings, both in continental lithosphere (Brittany, Iberia, Artic Canada, Central Asia, Alps, and Pannonian Basin) and in oceanic lithosphere (Indian Ocean).…”
Section: Introductionmentioning
confidence: 99%
“…Cloetingh et al, 1999Cloetingh et al, , 2002Stephenson and Cloetingh, 1991;Lambeck, 1983;McAdoo and Sandwell, 1985;Ziegler et al, 1995;Bonnet et al, 2000;Gerbault, 2000;Krishna et al, 2001) to put forward a process of deformation through buckling of the entire lithosphere (known as lithospheric folding). These have been found within intraplate settings, both in continental lithosphere (Brittany, Iberia, Artic Canada, Central Asia, Alps, and Pannonian Basin) and in oceanic lithosphere (Indian Ocean).…”
Section: Introductionmentioning
confidence: 99%
“…(35). Cloetingh and Burov (2011) compiled wavelengths of folded lithosphere, including crustal, mantle and whole lithosphere folding, for 17 regions worldwide, including Central Asia (Burov et al, 1993), central Australia (Lambeck, 1983b), the north-east European platform (Bourgeois et al, 2007), the Tibet/Himalayan syntaxes belt (Shin et al, 2015) and the Indian oceanic lithosphere (McAdoo and Sandwell, 1985;Krishna et al, 2001), and showed that all fold wavelengths are between 40 and 700 km. Not surprisingly, wavelengths for crustal folding are the smallest and wavelengths for whole lithosphere folding are the largest.…”
Section: Lithospheric Foldingmentioning
confidence: 99%
“…Throughout the Neogene, the Bengal Basin underwent significant multiphase deformation that resulted in the folding of the plate between the Ninetyeast Ridge and the 85°E Ridge (Krishna et al, 2001). In addition to the Miocene and Eocene unconformities (Curray et al, 2003), site survey data revealed two additional regional unconformities.…”
Section: Bengal Basin Deformationmentioning
confidence: 99%